The Role of Artificial Intelligence in Developing EFL and ESL Students' Critical Thinking A Systematic Literature Review - Nurhalisa, Hafidzah; Anjaniputra, Agung Ginanjar (EDUCAFL: Journal on Education of English as Foreign Language, 2025)
Artificial Intelligence’s contribution to supporting critical thinking in language learning has received significant attention. However, although the role of AI in English learning has been widely studied, studies specifically addressing the role and challenges of AI in developing critical thinking in ESL/EFL learners are still limited. Therefore, this study analyses the contribution and constraints of using AI in developing critical thinking through a systematic literature review (SLR) of 390 articles from the Scopus and ERIC databases published between 2023-2025. The findings indicate that AI contribute to develop critical thinking by providing rapid feedback, supporting learning, and strengthening higher order thinking skills. However, Ai integration also faces challenges such as overreliance and the perception that AI results are perfect, which encourage students to accepts answers without critical evaluation. These findings emphasize the important of using AI ethically and critically by providing students with strategies to examine and question AI generated content.